(untitled) (Research, Society and Development, 2021)
The aim of this study was to characterize the epidemiological profile of human anti-rabies treatment pre and post-exposure, in the city of Jataí, Goiás, in 2014. For this, a descriptive study was carried out regarding the human anti-rabies treatment included in the Notifiable Diseases Information System. These data were tabulated and analyzed in Microsoft Office Excel 2010 spreadsheets. There were 563 of human anti-rabies treatments in 2014, with a large majority residing in the urban area (98.4%). Of the total number of patients, 502 (89.16%) were in search of post-exposure prophylaxis, and of these injuries, the main type of exposure was bite (96%), hands / feet (39.24%), with 83.07% of single injuries accidents, and a predominance of deep wounds (90.64%). Regarding the aggressor animal, the most frequent species was canine (77.79%), 86.32% of the animals were healthy at the time of the accident, and 81.27% of them were observed. The most indicated treatment modality was the observation of the animal associated with the use of vaccine (78%), however, the effectiveness of the prescribed prophylaxis occurred in only 83.30% of the cases. It is concluded that the study contributed to the characterization and understanding of the epidemiological profile of human anti-rabies prophylaxis in the municipality, showing the importance of health education, the technical qualification of the professionals who provide care, and the constant necessity of epidemiological surveillance actions.